Kobiety piszą po kaszubsku – autorki i tematy. Szkic interpretacyjny - Kuik-Kalinowska, Adela (Slavia Occidentalis, 2017)
The article is dedicated to literature written by women in the Kashubian language. Notably, in Kashubian literature, recent decades have witnessed a revival in women’s writing, resulting in numerous literary works. There are several reasons for this, all determined predominantly by the cultural tradition of Kashubia. The revival in the literary world of female writers and poets most certainly results from numerous complex social and cultural processes, including the growing emancipation, the need for education and opening up to the world. Women writing in Kashubian express themselves in poetry, drama and prose. The works of women writing in Kashubian can be attributed to two stages originating in the 1980s. Among the first poets and writers were Rozalia Narloch (referred to as the “Kashubian Cinderella”), Teodora Kropidłowska, writing under the pseudonym “Deotyma” and Agnieszka Browarczyk. They were followed by the novels and plays by Anna Łajming. The most prominent female authors writing in Kashubian include Maria Boszke, Krystyna Muza, Jaromira Labuda, Ida Czaja, Hanna Makurat, Wanda Kiedrowska, Ewa Warmowska, Elżbieta Bugajna, Bożena Ugowska, Lucyna Sorn, Dorota Wilczewska and Gracjana Potrykus.